Irreversibility investigation of Casson fluid flow in an inclined channel subject to a Darcy-Forchheimer porous medium: a numerical study - Roja, A.; Gireesha, B. J.; Nagaraja, B. (Applied mathematics and mechanics, 2021)
The heat transfer and entropy generation characteristics of the magnetohydrodynamic Casson fluid flow through an inclined microchannel with convective boundary conditions are analyzed. Further, the effects of the viscous forces, Joule heating, heat source/sink, and radiation on the flow are taken into account. The non-dimensional transformations are used to solve the governing equations. Then, the reduced system is resolved by the fourth-fifth order Runge-Kutta-Fehlberg method along with the shooting technique. The effects of different physical parameters on the heat transfer and entropy generation are discussed in detail through graphs. From the perspective of numerical results, it is recognized that the production of entropy can be improved with the Joule heating, viscous dissipation, and convective heating aspects. It is concluded that the production of entropy is the maximum with increases in the Casson parameter, the angle of inclination, and the Hartmann number. Both the Reynolds number and the radiation parameter cause the dual impact on entropy generation.